Optimization of bleaching power by sulfuric acid activation of bentonite - BAYRAM, HALE (My University, 2021)
Abstract Acid activation was carried out by heating muds prepared from Ca-rich bentonite (CaB), sulfuric acid (H 2 SO 4 ) and distilled water, yielding various bleaching earths (BEs). The roles of each of the process variables, namely mass fraction of H 2 SO 4 ( x ) in the dried CaB and pure H 2 SO 4 mixture, heating temperature ( T ) and contact time ( t ), in the activation were tested. The raw CaB and each BE were examined with X-ray diffraction, chemical analyses, N 2 adsorption/desorption, pH-metry and tintometry. The BE contents in both the aqueous and oily suspensions were set to 2% by mass in order to measure the pH value and the bleaching power, respectively. The optimum conditions for the activation to obtain a BE having the same bleaching power (0.60) as Tonsil® Optimum Bleaching Earth for soybean oil were determined as x = 0.35, T = 100°C and t = 2 h. The bleaching power increased only marginally upon increasing the activation time from 2 h up to 10 h at a given x and T . After 10 h, significant changes did not take place in the bleaching power of the BE. The mass fraction of total structural metal oxide ( y ), pH value, specific pore volume ( V ), specific surface area ( S ) and mean internal diameter ( D ) of the mesopores for the optimized BE are y = 0.10, pH = 3.0, V = 0.31 cm 3 g –1 , S = 225 m 2 g –1 and D = 7 nm. The pH and D values were more important for bleaching the alkaline refined soybean oil compared to the other parameters tested.